2011
DOI: 10.1136/bmj.d3245
|View full text |Cite
|
Sign up to set email alerts
|

Management of severe sepsis in patients admitted to Asian intensive care units: prospective cohort study

Abstract: Objectives To assess the compliance of Asian intensive care units and hospitals to the Surviving Sepsis Campaign's resuscitation and management bundles. Secondary objectives were to evaluate the impact of compliance on mortality and the organisational characteristics of hospitals that were associated with higher compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
152
5
8

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 203 publications
(186 citation statements)
references
References 38 publications
(72 reference statements)
21
152
5
8
Order By: Relevance
“…A multicenter observational study conducted from September 2007 to October 2008 in 11 ICUs of Chinese teaching hospitals showed that the overall compliance during 6 h resuscitation and 24 h management bundles were 5.5% and 17.4%, respectively (20). Another study conducted in 150 ICUs in 16 Asian countries in July 2009 showed similar results (21). Currently, we can access all the advanced information from literature and scientific proceedings; however, the basic knowledge and skill training courses are inadequate.…”
Section: Mortality Of Sepsissupporting
confidence: 61%
“…A multicenter observational study conducted from September 2007 to October 2008 in 11 ICUs of Chinese teaching hospitals showed that the overall compliance during 6 h resuscitation and 24 h management bundles were 5.5% and 17.4%, respectively (20). Another study conducted in 150 ICUs in 16 Asian countries in July 2009 showed similar results (21). Currently, we can access all the advanced information from literature and scientific proceedings; however, the basic knowledge and skill training courses are inadequate.…”
Section: Mortality Of Sepsissupporting
confidence: 61%
“…14 MOSAICS study in medical ICUs of Asian countries reported a mortality of 44.5%. 15 A prospective study by INDICAP in Indian medical ICUs also reported a high mortality in different parts of the country. 16 Our study reported a mortality of 11.5% and 11.2% were transferred to palliative care/ transferred to other hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Poor clinical outcomes are related to many factors including patient factors such as malnutrition, lack of readily available resources to appropriately triage, diagnose and treat sepsis, and suboptimal adherence to specific sepsis management guidelines (3)(4)(5)(6)(7)(8)(9). Even as evidence-based protocols directed at managing sepsis in resource dense and resource poor environments have emerged, the promise of reduced mortality has been difficult to realize (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%